Impact of Increased Imports of Agricultural Products due to FTAs on Domestic Price Decline - 정민국 (한국농촌경제연구원, 2017)
The purpose of this paper is to propose a method of estimating the import contribution rate. The import contribution is a factor that should be considered in calculating the direct payment for damage. The decline in prices is caused by the combination of various factors. In this case, the decomposition of various factors can confirm the price drop due to the increase in imports. To this end, we set up a partial equilibrium model for individual markets and decompose various factors contributing to the price decline using the equilibrium displacement model. Various types of elasticities are needed to calculate the import contribution rate derived from EDM. Because elasticity has a wide spectrum depending on the purpose of the study or the data used, a cautious approach is needed to obtain objective figures.
Keywords: import contribution rate; equilibrium displacement model; price elasticity; direct payment for damage; import contribution rate; equilibrium displacement model; price elasticity; direct payment for damage